Knowledge gaps in the IPCC Sixth Assessment Report (AR6) around livestock in Africa - Cramer, Laura K.; Gosling, Amanda (2024)
Adverse climate change impacts on livestock health and productivity are already occurring in Africa, and future livestock production is also at risk but there is a lack of detailed supporting evidence. There is adequate research in areas such as livestock heat stress, and some research has been conducted on rangelands net primary productivity, the development of emission factors for African breeds and systems, and risks to aquatic systems but significant research gaps remain. Long-term funding commitments are needed to build additional research capacity, develop local livestock production system emissions factors and prioritise government data collection and analysis.